A PROJECT WORK REPORT ON Green House Machine - Lama Kharaz; Seema Ziyad (My University, 2022)
We made a machine that includes a group of seedlings and their types, and provides the seedlings with the appropriate conditions in terms of measuring temperature and humidity in addition to the lighting system and the fire protection system. And we did a store that initially relied on a touch screen (nextion) and a login card, so the user entered his card via RFID, and then his data appeared on the screen, and through it he entered the number of seedlings to be purchased and the type after making sure that the order was accepted, the order will be successfully finished and the door will opened ,as well as The system is based on the principle of using humidity and temperature sensors to check the appropriate conditions for the seedlings, , when the temperature exceeds the required value and the humidity is low, the fan and humidifier are turned on until the required value is reached. In addition to the fire protection system, if there is a fire on the farm, the system will call the administrator and activate the night lighting system, so that in the dark this idea is not available in Palestine, it is similar and close to the idea of a vending machine We were able to set up the system almost successfully, but we encountered difficulties in the mechanical part and everything that was mentioned above was implemented.